Economic implications of the IEA efficient world scenario - Chateau, Jean; Magné, Bertrand; Cozzi, Laura (Paris, 2014)
"In its 2012 edition of the World Energy Outlook, the International Energy Agency (IEA) produced an Efficient World Scenario (IEA, 2012) to assess how implementing only economically viable energy efficiency measures would affect energy markets, investment and greenhouse emissions (GHG). The IEA analysis found that in order to halve global primary energy demand over 2010-2035, additional investments of USD 11.8 trillion in more efficient end-use technologies would be necessary. Using the OECD ENV-Linkages macro-economic model, this report simulates the economic and environmental impacts which the IEA Efficient World Scenario implies..."